Business model innovation strategy transformational concepts and tools for entrepreneurial leaders - Amit, Raphael 1947-; Zott, Christoph 1967- (John Wiley & Sons, Inc., 2021)
The emergence of business model innovation as a key strategic issue that both founders of new firms and senior managers of incumbent firms need to address has created a teaching need in business schools. Yet, as of now, there is no book on the market that provides systematic and focused course materials. As thought leaders on business model innovation strategy, Amit and Zott frequently receive requests from around the world for teaching materials on the subject. Business Model Innovation Strategy is targeted at the following two market segments: (i) the academic market and (ii) the trade market. In the academic market, the book constitutes a full semester textbook targeted at MBA, EMBA, and senior undergraduate courses in strategy and entrepreneurship, globally. In the trade market, the book provides readers with state-of-the art and action-oriented guidance on the role of business model innovation in the determination of the viability and prosperity of their businesses"--Provided by publisher.